The effects of heat treatment upon the shock response of a copper-beryllium alloy. (15th February 2019) - Millett, J.C.F.; Whiteman, G.; Park, N.T.; Case, S.; Appleby-Thomas, G.
Abstract: The mechanical response of a copper-2 wt% beryllium alloy in either a solution treated or aged condition has been investigated within the shock loading regime. In terms of Hugoniot Elastic Limit, shear strength and spall (dynamic tensile) strength, the material in the aged condition has been observed to be significantly stronger than when in the solution treated state. Whilst these trends are the same as when tested under quasi-static conditions, the level of strengthening due to shock loading is less than during quasi-static loading. It is believed that the distribution of non-shearable particles within the microstructure (caused by aging) restrict the ability of the material to deform via dislocation motion and generation, which in turn reduces strain-rate sensitivity. Thus the relative differences in strength between aged and solution treated materials will be less under shock loading conditions compared to quasi-static conditions. In contrast, strong similarities between the shear strengths of the solution treated material and pure copper were noted. It has been suggested that twinning in the alloy may be responsible (due to the small contribution of twins to shock induced strengthening), although comparison of partial dislocation separation between the two materials suggest otherwise.